2021
DOI: 10.1209/0295-5075/ac24c1
|View full text |Cite
|
Sign up to set email alerts
|

Joule-Thomson expansion for noncommutative uncharged black holes

Abstract: In this work we study the Joule-Thomson expansion for uncharged black holes in a noncommutative scenario characterized by a parameter θ, which is present in the horizon function. We calculate the inversion temperature for some values of θ and the isenthalpics for fixed masses. We find that the uncharged noncommutative black hole behaves as a charged commutative one.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Given this choice of mass distribution, the corresponding BH solution was studied in [1347] by constructing the (covariantly conserved) energy-momentum tensor corresponding to the energy density of equation (135). The final result is that the metric function describing NCG-inspired BHs within this scenario is given by [1347] (see also [1348][1349][1350][1351][1352][1353][1354][1355][1356][1357][1358][1359][1360][1361][1362] for further works on NCGinspired BHs):…”
Section: Non-commutative Geometrymentioning
confidence: 99%
“…Given this choice of mass distribution, the corresponding BH solution was studied in [1347] by constructing the (covariantly conserved) energy-momentum tensor corresponding to the energy density of equation (135). The final result is that the metric function describing NCG-inspired BHs within this scenario is given by [1347] (see also [1348][1349][1350][1351][1352][1353][1354][1355][1356][1357][1358][1359][1360][1361][1362] for further works on NCGinspired BHs):…”
Section: Non-commutative Geometrymentioning
confidence: 99%
“…[ 46 ] These works indicated that, different from the van der Waals‐like fluid, the black hole in the AdS space has only a minimum inversion temperature, without a maximum one. The successive studies in various extended theories of gravity further confirmed these conclusions, [ 47–84 ] and the basic reason is the slight difference between the EoS of the black hole and the van der Waals‐like fluid.…”
Section: Introductionmentioning
confidence: 75%
“…Apart from these, there are several recent studies dealing with Joule-Thomson expansion of black holes in different theories of gravity. [23][24][25][26][27] Being motivated by these studies, in this work, we have considered the Joule-Thomson expansion of a charged anti-de Sitter black hole in the framework of Rastall gravity. In this paper, we shall consider a charged anti-de Sitter black hole surrounded by a quintessence field which has not been considered till now for the study of Joule-Thomson expansion to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%